Creating value through relationship building in a globalized marketplace / Sanjiv S. Dugal and Matthew H. Roy - S. Dugal, Sanjiv; Matthew, H. Roy (Faculty of Business and Management ; UiTM Press, 2002)
Information technology has altered our experience of space, time, and the nature of competition across the world. Competitive strategy includes collaboration and involves giving consumers around the world the opportunity to create their own value. To succeed at producing mass-customized products, businesses must have flexibility to enter ever-shifting markets, and maintain the reputation of the virtualness of their products across the planet. Managing reputation and identity become key challenges in the new global order.